Influence of the size of iron nanoclusters on their magnetization - Kveglis, L.I.; Noskov, F.M.; Kalitova, A.A.; Nasibullin, R.T.; Nyavro, A.V.; Cherepanov, A.N.; Olekhnovich, A.E.; Saprykin, D.N. (Karagandy University of the name of acad. E.A. Buketov, 2022)
The size of iron nanocrystals significantly affects the value of their magnetization. However, an adequate model of the structure of nanocrystalline formations comprising different numbers of iron atoms still does not exist. In this work, spatial models of nanocrystalline iron clusters differing in configuration and the number of their constituent atoms are constructed. Tetrahedrally close-packed cluster assemblies of iron atoms are taken as the basis for the proposed structures of nanocrystals. The spectra of the density of electronic states for the proposed clusters are constructed using the theory of the electron density functional. The calculation was carried out by the method of scattered waves in accordance with the band theory of crystals. The appearance of magnetization in tetrahedral close-packed cluster formations is associated with excited electronic states of atoms located on the surface of the nanocluster. Excited atoms have an increased electron density, that is, electrons are able to transition to states with higher energy, approaching the Fermi energy. In this case, the Stoner criterion necessary for the occurrence of magnetization is fulfilled. The configurations of electrons with spin up and down differ, which is why uncompensated magnetic moments appear. It is shown that the proposed models of iron nanoclusters are in satisfactory agreement with the known experimental data.
Темір нанокластары мөлшеріне олардың магниттелуінің әсері
Влияние размера нанокластеров железа на их намагниченность
Keywords: iron nanocluster; tetrahedrally tightly packed structures; magnetic properties.